Interface hardness analysis of between IN625 and CoCrMo manufactured by pulsed wave laser powder bed fusion - Hoo, Zhiong Sheng (2024)
The nuclear and petrochemical industries often require multi-metal parts that are corrosion-resistant, heat-resistant, and possess high strength to enhance equipment safety and reduce downtime. Additive manufacturing technology enables the rapid and flexible processing of multi-metal parts to meet these stringent demands. This study is aimed at investigating the interface hardness between CoCrMo/IN625 to determine optimal processing parameters that can be utilized in manufacturing reliable and durable multi-metal parts. The result indicates that when the volumetric energy density, Ev, is at or below 20 J/mm3, microfluidic forces are unable to sufficiently diffuse between the two metals, leading to insufficient diffusion, and the high hardness CoCrMo acts as a support, resulting in a significantly higher interface hardness. As Ev increases, intense recoil pressure within the microfluidic forces disrupts the melt pool, allowing for full diffusion between the two metals. The fully diffused high-hardness CoCrMo has been diluted by the low-hardness IN625, thus reducing the interface hardness. Considering the interface hardness, strength, and printing efficiency (time and energy consumption), we recommend a range of 35 J/mm3 < Ev ≤ 75 J/mm3. In this range, the average values for interface hardness and tensile strength of the samples are approximately 382 HV and 903 MPa, respectively.